Resistance of Rice Varieties to the Stored-Product Insect, Sitophilus zeamais (Coleoptera: Curculionidae). Issue 1 (10th September 2015) - Antunes, Catarina; Mendes, Raquel; Lima, Arlindo; Barros, Graça; Fields, Paul; Da Costa, Luísa Beirão; Rodrigues, José Carlos; Silva, Maria José; Correia, Augusto Manuel; Carvalho, Maria Otilia
Abstract : Four common Portuguese rice varieties—Thaibonnet, Gladio, Albatros, and Eurosis—were tested for their relative susceptibility to Sitophilus zeamais Motschulsky, a common pest of stored rice in Portugal and in tropical countries. Physical (moisture content, hardness, length, and width) and chemical (by attenuated total reflection-Fourier transform infrared spectroscopy) properties of rice kernels were measured. Insect bioassays measured median developmental time, Dobie's index of susceptibility, percentage of damaged grains and weight loss, and progeny developed. This was done for paddy, brown rice, and polished rice for each variety. There were small, but significant, differences in insect resistance among the varieties. However, it was different for paddy and polished rice. In paddy, these differences were correlated with hull damage, and Eurosis was the most susceptible variety. In polished rice, resistance was correlated with hardness, and Thaibonnet was the most susceptible variety. In general, paddy rice was more resistant to insect attack, followed by polished rice and then brown rice. Paddy kernels selected with undamaged hull were completely resistant to attack. Implications for IPM and breeding for resistant varieties are discussed.